2018
DOI: 10.1111/imj.13796
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin level and abnormal corrected QT interval in patients with coronary artery disease and chronic kidney disease

Abstract: Concentrations of serum albumin were significantly lower in the patients with an abnormal QTc interval and were associated with QTc prolongation. Further studies are needed to clarify whether lower serum albumin plays a role in the pathogenesis of QTc prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…[32,33] Toma et al and Wu et al showed that prolonged QT intervals and T accentuated deceleration of the T wave correlated with hypoalbuminemia. [13,34] In this study, the DLM could predict the development of hypoalbuminemia. The DLM may detect structural and physiological changes that affect the vulnerability of hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…[32,33] Toma et al and Wu et al showed that prolonged QT intervals and T accentuated deceleration of the T wave correlated with hypoalbuminemia. [13,34] In this study, the DLM could predict the development of hypoalbuminemia. The DLM may detect structural and physiological changes that affect the vulnerability of hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 84%
“…[4,5] Therefore, the detection of hypoalbuminemia is important to not only monitor nutritional and homeostasis general conditions, but also early-diagnose other diverse diseases using hypoalbuminemia as a surrogate factor and detect deterioration of the patient. [11][12][13][14][15][16] Although laboratory tests for albumin are diagnostic tests for hypoalbuminemia, they require blood sampling and infrastructure for a blood analysis. Therefore, the detection of hypoalbuminemia based on laboratory tests could not be used in daily life and low-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al reported that concentrations of serum albumin were significantly lower in patients with an abnormal QTc interval and were associated with QTc prolongation. Hypoalbuminemia may be a marker of comorbidity burden, a low serum albumin level may reflects an inflammatory burden leading to heart failure [30] . A low albumin level is associated with inflammation, and impaired synthetic function of liver and this has been linked to diastolic dysfunction in humans which indicate the association between inflammation and ventricular arrhythmias [31] .…”
Section: Discussionmentioning
confidence: 99%